VD_FINDINFO HC / 2013 / 582 vom 20. September 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, BAIL À LOYER, LOYER, TERME COMMINATOIRE, SOMMATION, LOCAL PROFESSIONNEL | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 257 CPC (CH)